2018
DOI: 10.3389/fenrg.2018.00072
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Poly(3,4-ethylenedioxythiophene) Polystyrene Sulfonate Polymer Coated Cathode for the Microbial Electrosynthesis of Acetate From Carbon Dioxide

Abstract: Microbial electrosynthesis (MES) is a bioelectrochemical technology developed for the conversion of carbon dioxide and electric energy into multicarbon chemicals of interest. As with other biotechnologies, achieving high production rate is a prerequisite for scaling up. In this study, we report the development of a novel cathode for MES, which was fabricated by coating carbon cloth with conductive poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) polymer. Sporomusa ovata-driven MES reactors eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In recent years, research efforts have been carried out to increase the productivity of MES systems for potential scaling up. Microbial catalysts, growth medium, and cathodes are all components of MES reactors that have been studied and optimized [9][10][11][12][13][14][15][16][17][18]. Electron transfer from the cathode to microbes is at the core of MES and multiple strategies have pursued the development of novel electrode materials and spatial arrangements to improve it.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, research efforts have been carried out to increase the productivity of MES systems for potential scaling up. Microbial catalysts, growth medium, and cathodes are all components of MES reactors that have been studied and optimized [9][10][11][12][13][14][15][16][17][18]. Electron transfer from the cathode to microbes is at the core of MES and multiple strategies have pursued the development of novel electrode materials and spatial arrangements to improve it.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To study the possible correlation between microbial alterations and H 2 evolution in a MES system, a hydrogen microsensor was placed in close proximity to the surface of a cathode set at different potentials to measure H 2 evolution in situ in the presence of sterile medium, bacterial culture or cell-free filtrate. Sporomusa ovata, one of the best pure culture MES catalysts for the production of acetate from CO 2 [38,39] is used here as a model because of its capacity to perform MES over a large range of cathode potential [3,[40][41][42][43][44][45][46]. In order to further understand H 2 evolution and electron uptake during MES, other variables were investigated, including the presence of metals at the cathode surface as well as the presence of hydrogenases and other enzymes in the cell-free spent medium.…”
Section: Introductionmentioning
confidence: 99%
“…Sporomusa ovata grown on cathodes use the electrode as an electron source and CO 2 as the carbon source to sustain their autotrophic metabolism. We found that pre-cultures for bioelectrochemical experiments are also grown autotrophically under H 2 and CO 2 conditions ( Aryal et al, 2016 , 2017b , 2018 , 2019 ; Chen et al, 2016 ). We have not found any published study inoculating bioelectrochemical experiments directly from a betaine grown S. ovata culture.…”
Section: The Genus Sporomusamentioning
confidence: 95%
“… Acetate production rates of S. ovata with different electrode materials. Bars of the same color are derived from the same studies: [1]: ( Aryal et al, 2019 ), [2]: ( Aryal et al, 2016 ), [3]: ( Bian et al, 2018 ), [4]: ( Li et al, 2018 ), [5]: ( Cui et al, 2017 ), [6]: ( Aryal et al, 2017a ), [7]: ( Aryal et al, 2018 ), [8]: ( Aryal et al, 2016 ), [9]: ( Gong et al, 2013 ), [10]: ( Zhang et al, 2013 ). On that basis, the same color results are directly comparable, as other parameters (cathode potential, medium, temperature, reference for normalization) are equal.…”
Section: Optimization Strategies Aiming To Enhance Bioelectrochemical...mentioning
confidence: 99%